The durability of fly ash concrete in marine and softwater environments - Mackechnie, James Ronald (Department of Civil Engineering, 2016)
Concrete is attacked by aggressive agents in the marine and softwater environments which reduce the durability of concrete. To help lessen the effect of this aggressive attack, fly ash concrete has been recommended for use in these environments. The lower permeability, increased chemical resistance and higher long-term strength of fly ash concrete are expected to improve the concrete durability. In this research the effect of fly ash was investigated with regard, initially to general concrete properties such as bleeding, early set, workability, mortar excess and compressive strength. Lethabo field 2 fly ash and Western Cape materials were used for this work. Having developed a wide range of concrete mixes, further investigation was done into specific concrete properties such as the effect of different curing regimes, water absorption, permeability and freeze-thaw resistance. These properties are considered to have an influence on concrete durability. Comparisons were made between the concrete properties of Lethabo field 2, Lethabo classified and Matla classified fly ash concrete. The three types of concrete were tested for compressive strength, sorptivity (rate of water absorption) and density. At the same time, fly ash and OPC concrete samples were exposed to the marine and softwater environment for up to 10 months. Marine exposure was done in the submerged, tidal and spray zones in Table Bay. Softwater exposure was done at Constantia Nek and Steenbras Water Treatment Plants. The performance of concrete in the various exposure conditions was measured by compressive strength, sorptivity and density tests. Fly ash improved many of the properties of concrete, with fly ash concrete having better workability, higher long-term strength, reduced bleeding, lower sorptivity and reduced permeability than similar OPC concrete. Some of the properties of concrete were however worsened by using fly ash. Fly ash concrete had longer setting times, reduced resistance to freezing and thawing and was more adversely affected by dry curing than similar OPC concrete. Lethabo field 2 fly ash concrete had higher compressive strength and lower sorptivity than either Lethabo classified or Matla classified fly ash concrete. The long-term performance of Lethabo classified and Matla classified fly ash concrete was better than that of Lethabo field 2 fly ash concrete, with regard to compressive strength development and sorptivity reduction. Fly ash concrete performed well in both the marine and softwater environments. After 10 months of exposure in either marine or softwater conditions, fly ash concrete had higher compressive strength and lower sorptivity than similar OPC concrete. The good performance of fly ash concrete in the marine and softwater environment confirmed the ability of fly ash to improve many of the important durability properties of concrete. From this medium-term durability investigation it was found that Lethabo field 2 fly ash improved the performance of concrete in marine and softwater environments while fly ash, in general, improved many of the durability properties of concrete.